Localised Chronic Fibrosing Vasculitis in a 6 Year Old Boy Clinically Mimicking Dermatofibrosarcoma Protuberans - Michela Brena; Italo Francesco Aromolo; Nicola Adriano Monzani; Stefano Cambiaghi; Giorgio Alberto Croci; Chiara Benaglia; Riccardo Cavalli (JEADV Clinical Practice)
ABSTRACT This case outlines the stepwise evaluation of a growing plaque on the back of a 6‐year‐old boy mimicking dermatofibrosarcoma protuberans. Further investigations, including echography and two biopsies, led to the unexpected diagnosis of Localised Chronic Fibrosing Vasculitis, highlighting the importance of considering rare entities in challenging cases.